Human Pathogen Colonization of Lettuce Dependent Upon Plant Genotype and Defense Response Activation - Jacob, Cristián; Melotto, Maeli (Frontiers in Plant Science, 2020)
Abstract. Fresh produce contaminated with human pathogens may result in foodborne disease outbreaks that cause a significant number of illnesses, hospitalizations, and death episodes affecting both public health and the agribusiness every year. The ability of these pathogens to survive throughout the food production chain is remarkable. Using a genetic approach, we observed that leaf colonization by Salmonella enterica serovar Typhimurium 14028s (S. Typhimuriumm 14028s) and Escherichia coli O157:H7 (O157:H7) was significantly affected by genetic diversity of lettuce (Lactuca sativa L. and L. serriola L.). In particular, there was a significant variation among 11 lettuce genotypes in bacterial attachment, internalization, and apoplastic persistence after surface- and syringe-inoculation methods. We observed a significant correlation of the bacterial leaf internalization rate with stomatal pore traits (width and area). Moreover, bacterial apoplastic populations significantly decreased in 9 out of 11 lettuce genotypes after 10 days of surface inoculation. However, after syringe infiltration, populations of E. coli O157:H7 and S. Typhimurium Tm 14028s showed positive, neutral, or negative net growth in a 10-day experimental period among seedlings of different lettuce types. The relative ability of the bacteria to persist in the apoplast of lettuce genotypes after syringe inoculation was minimally altered when assessed during a longer period (20 days) using 3.5- to 4-week-old plants. Interestingly, contrasting bacterial persistence in the lettuce genotypes Red Tide and Lollo Rossa was positively correlated with significant differences in the level of reactive oxygen species burst and callose deposition against S. Typhimurium Tm 14028s and E. coli O157:H7 related to plant defense responses. Overall, we identified characterized the genetic diversity in the interaction between lettuce genotypes and enterobacteria S. Typhimurium STm 14028s and E. coli O157:H7, and discovered that this genetic diversity is linked to variations in plant immune responses towards these bacteria. These results provide opportunities to capitalize on plant genetics to reduce pathogen contamination of leaves.